InGaN laser diodes emitting at 500 nm with p-layers grown by molecular beam epitaxy. (26th January 2015) - Malinverni, Marco; Lamy, Jean-Michel; Martin, Denis; Lahourcade, Lise; Feltin, Eric; Dorsaz, Julien; Castiglia, Antonino; Rossetti, Marco; Duelk, Marcus; Vélez, Christian; Grandjean, Nicolas
Abstract: We demonstrate hybrid laser diodes by combining n-type layers and an active region grown by metal–organic vapor phase epitaxy with p-type layers grown by molecular beam epitaxy. These p-doped layers, grown at 740 °C, exhibit state-of-the-art electrical characteristics and prevent the indium-rich quantum wells from thermal degradation. Narrow ridge-waveguide lasers with high-reflectivity coatings show a threshold current density of 9.7 kA·cm −2, a threshold voltage of 5.4 V, and a lasing wavelength of 501 nm. The internal optical loss and material gain of the epitaxial structures are also measured and discussed.